Nutritional and microbiological dynamics in the preparation of prahoc fish paste. - Channmuny Thanh; Sylvie Avallone; Vincent Chochois; Caroline Douny; Kevin Bethune; Hasika Mith; Chanthol Peng; Adrien Servent; Ingrid Collombel (PLoS ONE)
Prahoc is a traditional fermented fish widely consumed in Cambodia. Nevertheless, the processing and nutritional values of this daily-consumed product were poorly described. This study offers a detailed analysis of the biochemistry, nutritional composition, and microbiota during the six-month Prahoc incubation. Macronutrients (e.g. lipids, proteins) are rather well preserved during the preparation of the fish paste but the fatty acid and amino acid profiles are slightly modified at the end of the unit operation. Free amino acids increased, which facilitates the in vitro digestibility of the final paste, while beneficial fatty acids, such as eicosapentaenoic and docosahexaenoic acids, decreased. At the end of the process, the peroxide value was nearly five times greater than the limit set by the Codex Alimentarius (10 meq O2/kg). Biogenic amines, particularly cadaverine, were present but remained within acceptable limits. Metabarcoding analysis revealed that salt-tolerant bacteria dominated the fermentation process, while fungal activity was minimal. Lactic acid bacteria, such as Vagococcus and Streptococcus, were predominant before salt addition, while the fish pathogen Aeromonas established itself immediately after. Clostridium remained steady throughout, and Lentibacillus became dominant after six months. Food safety concerns related to biogenic amines, peroxides, and Clostridium highlight the need for establishing standard operational practices among national processors to mitigate food risks.